Seasonal and interannual variability of water masses in Drake passage - Artamonov, Yu. V.; Skripaleva, E. A.; Fedirko, A. V. (Ukrainian Antarctic Journal, 2012)
On the basis of climatic array World Ocean Atlas-2009, archive data bases World Ocean Data-2009 and the data of re-analysis NCEP the seasonal and interannual variability of water masses in Drake Passage and adjacent water areas of Southern ocean is investigated. The connection of water masses spatial-temporal variability with position, large-scale fronts and indexes of atmospheric circulation variability is analyzed.